2015
DOI: 10.1080/13642987.2015.1019219
|View full text |Cite
|
Sign up to set email alerts
|

Extreme energy, ‘fracking’ and human rights: a new field for human rights impact assessments?

Abstract: This article explores the potential human rights impacts of the 'extreme energy' process, specifically focussing on the production of shale gas, coal-bed methane (CBM) and 'tight oil', known colloquially as 'fracking'. The article locates the discussion within a broader context of resource depletion, the 'limits to growth' and the process of extreme energy itself. Utilising recent secondary data from the United States and Australia, combined with the preliminary findings of our ethnographic fieldwork in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…These studies have led some authors to argue for an ethical analysis of shale gas production (de Melo-Martin et al 2014, Field et al 2014, North et al 2014, Short et al 2015, Wheeler et al 2015. In particular, some have argued that shale gas production raises issues of environmental justice (Carre 2012, Perry 2012, US Environmental Protection Agency (EPA) 2012, Fry et al 2015, Ogneva-Himmelberger and Huang 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have led some authors to argue for an ethical analysis of shale gas production (de Melo-Martin et al 2014, Field et al 2014, North et al 2014, Short et al 2015, Wheeler et al 2015. In particular, some have argued that shale gas production raises issues of environmental justice (Carre 2012, Perry 2012, US Environmental Protection Agency (EPA) 2012, Fry et al 2015, Ogneva-Himmelberger and Huang 2015.…”
Section: Introductionmentioning
confidence: 99%
“…We might usefully distinguish three types of environmental justice concern. First, on a rights-based conception of environmental justice, we should be concerned if anyone suffers significant harm as a result of shale gas production (Agyeman 2005, Short et al 2015). Second, on an equity-based or distributive conception, we should be concerned if the distribution of hazards and/or benefits associated with shale gas production is unfair (Bell, 2004, Fry et al 2015, Ogneva-Himmelberger and Huang 2015.…”
Section: Introductionmentioning
confidence: 99%
“…by Short et al, 33 namely in the mishandling of human rights in the context of energy extraction. The implications that can be interpreted from the findings in the article by Short et al, based on the gathered information from antifracking protesters in the United Kingdom, Europe and elsewhere, is that despite the inclusion of human rights language or objectives in company policy or CSR statements, human rights continue to be maligned in the pursuit of big business interests.…”
Section: The Special Issuementioning
confidence: 99%
“…While this technological innovation has clearly contributed significantly to the economic prowess of the United States (at least in fossil fuel terms), it has led to many instances of social (Hirsch et al 2018), environmental (Hernandez 2018;Jackson et al 2014), and non-human animal harms (Bamberger and Oswald 2015). This has resulted in the recent labelling of UHF as a form of extreme energy (Hulme and Short 2014;Short et al 2015;Short and Szolucha 2017). Table 1 Principles of Earth jurisprudence.…”
Section: Unconventional Hydraulic Fracturing (Uhf) For Shale Gas In Tmentioning
confidence: 99%
“…Academics in both the social sciences (e.g., Cotton 2017;Lampkin 2016Lampkin , 2019Short et al 2015) and hard sciences (e.g., Jackson et al 2014) have concluded that UHF in the UK poses several different risks to the environment. Before outlining three of these potential risks, it is important to note that they may not apply to all cases of UHF due to the UK's complex underlying geology (Loveless et al 2018).…”
Section: Three Major Environmental Risks Surrounding Fracking In the Ukmentioning
confidence: 99%